The drivers of technology adoption on tobacco agribusiness in West Nusa Tenggara - Eka Nurjati; Achsanah Hidayatina; Ikval Suardi; Umi Karomah Yaumidin (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
West Nusa Tenggara (NTB) is the third-largest tobacco-producing province in Indonesia. However, the dynamics of tobacco production tend to decline, one of which is due to its productivity and land area, which also tends to stagnate. Technology is one of the levers of productivity and the efficiency and effectiveness of supply chain management. The objectives of this research are to assess the level of technology adoption, analyze the factors influencing farmers' decisions to adopt technology, and develop policy recommendations based on the findings. This research uses mixed methods, namely qualitative and quantitative. The qualitative approach uses an in-depth interview approach and Focus Group Discussion (FGD) with farmers and stakeholders of the tobacco industry. The quantitative approach uses the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results showed that farmers who used tractors, ovens, tobacco pressing, power weeder, and combine harvester technology were 42%, 71%, 46%, 21%, and 2%, respectively. The results of PLS-SEM analysis showed that the variables of education and age had a positive and significant effect on the adoption of tobacco farmer technology. In contrast, the variables of length of farming and land area did not have a significant effect. The variables of land area, length of farming experience, and farmers' age do not significantly affect technology adoption. Based on the results of this study, several strategies to increase technology adoption for tobacco farmers are institutional strengthening to facilitate socialization and counseling related to technology, the establishment of financing schemes that are friendly to farmers, and the development of research and innovation related to appropriate technology to economic, social, cultural, and environmental aspects.